EFEKTIVITAS MODEL PEMBELAJARAN KOMUNIKASI KESEHATAN BERBASIS PENDIDIKAN KARAKTER TERHADAP PENINGKATAN PRESTASI BELAJAR MAHASISWA KEBIDANAN - Noorbaya, Siti; Mutmainnah, Annisa Ul; Amriana, Mita (Jurnal Kebidanan Mutiara Mahakam, 2019)
Health communication is one of the core compulsory subjects for midwifery students. The character-based health communication learning model is a study with the aim to find out the effectiveness of the character education-based health communication learning model with a specific target of improving student achievement. In this study the method used was Pre-Experimental with Posttest Only Control Group Design with a sample of 70 students divided into 2 groups: 35 treatment group respondents and 35 control group respondents. The results of the study of the effectiveness of health education learning models based on character education on improving learning achievement, interpretation of the results of the normality test data of the treatment group has a sig value of 0.200> 0.05, and the control group has a sig value of 0.129> 0.05, meaning that the data is normally distributed. Results of Data Analysis using the Independent Sample T-Test of 0.035 <0.05, there is a significant difference between the learning outcomes of the experimental / treatment group and the control group. Fromthe results of the study it can be concluded that the character-based health communication learning model given to midwifery students can improve student learning achievement